Assessment of Fish Protein Hydrolysates in Juvenile Largemouth Bass (Micropterus salmoides) Diets: Effect on Growth, Intestinal Antioxidant Status, Immunity, and Microflora - Fan, Ze; Wu, Di; Li, Jinnan; Zhang, Yuanyuan; Cui, Zhiying; Li, Tianbi; Zheng, Xianhu; Liu, Hongbai; Wang, Liansheng; Li, Hongqin (Frontiers in Nutrition, 2022)
Varying dietary inclusion levels of fish protein hydrolysates (FPH) were applied in a feeding experiment with juvenile largemouth bass (Micropterus salmoides) to assess their effects on growth, intestinal antioxidant status, immunity, and microflora. FPH were added in 4 dietary levels: 0 g/kg (control group, FPH-0), 10 g/kg (FPH-10), 30 g/kg (FPH-30), and 50 g/kg (FPH-50) dry matter, respectively substituting 0, 5.3, 16.3, and 27.3% of fish meal with dietary fish meal. Quadruplicate groups of 25 juvenile largemouth bass with initial body weight 9.51 ± 0.03 g were fed during the 56-day feeding experiment. Experimental results showed that fish fed FPH-30 obtained a significantly higher weight gain rate (WGR), specific growth rate (SGR), protein efficiency ratio (PER), and significant feed conversion rate (FCR) compared to the other three groups (P < 0.05). FPH-30 group also promoted protein synthesis and deposition, as evidenced by the higher whole-body crude protein contents, the higher expressions of GH1, IGF-1, TOR, and S6K in the liver, and SLC7A5, SLC7A8, SLC38A2, and SLC15A2 in the intestine than the other three groups. FPH-30 group could also enhance intestinal health status by increasing the activities of SOD, POD, CAT, GSH-Px, and T-AOC activities by upregulating the expressions of SOD, GSH-Px, IL1β, and TNFβ, and by reducing the MDA contents and the expressions of IL15, Caspase 3, Caspase 9, and Caspase 10 than other groups. Compared to the control group, the Actinobacteriota abundance markedly decreased in FPH treatments, while the variation tendency of the phylum Proteobacteria was opposite. The peak value of Firmicutes:Bacteroidetes ratio and the lowest of Bacteroidetes abundance were seen in largemouth bass fed FPH-30 (P < 0.05). Fish in three FPH treatments had lower abundances of opportunistic pathogens Staphylococcus and Plesiomonas than fish in the control group. In conclusion, FPH is a nutritious feed ingredient for juvenile largemouth bass, and can be added to a dietary level of 30 g/kg dry matter replacing fish meal without any negative effect on growth and feed utilization. FPH supplements could also strengthen the intestinal immune mechanisms of largemouth bass to tackle the immunodeficiency produced by fish meal replacement.